PENINGKATAN KINERJA MELALUI DISIPLIN DAN LINGKUNGAN KERJA FISIK (STUDI EMPIRIK PADA KARYAWAN PENYEDIA JASA LAINNYA PERORANGAN RSPON PROF DR MAHAR MARDJONO JAKARTA - Novita Febriana; Ading Sunarto (Yayasan Education and Social Center, 2026)
This study aims to examine the effect of work discipline and physical work environment on the performance of PJLP (Individual Other Service Providers) employees at RS PON Prof. Dr. dr. Mahar Mardjono Jakarta. This research used a quantitative method with an associative approach. The sample consisted of 83 respondents selected using a saturated sampling technique. Data were collected through questionnaires and direct field observations. The data analysis techniques included validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, coefficient of determination, and hypothesis testing (t-test and F-test) using IBM SPSS version 27. The results of the study show that the regression equation obtained was Y = 5.167 + 0.856X₁ + 0.066X₂. Work discipline has a positive and significant effect on employee performance with a significance value of 0.000 < 0.05, while the physical work environment partially does not have a significant effect with a significance value of 0.538 > 0.05. However, simultaneously, work discipline and physical work environment have a significant effect on employee performance with a significance value of 0.000 < 0.05. The coefficient of determination (R² = 0.561) indicates that 56.1% of the variation in employee performance can be explained by work discipline and physical work environment, while the remaining variation is influenced by other factors outside this study.